Chronic kidney disease and subclinical abnormalities of left heart mechanics in the community. Issue 3 (16th November 2021) - Iwama, Kentaro; Nakanishi, Koki; Daimon, Masao; Yoshida, Yuriko; Sawada, Naoko; Hirose, Kazutoshi; Yamamoto, Yuko; Ishiwata, Jumpei; Hirokawa, Megumi; Kaneko, Hidehiro; Nakao, Tomoko; Mizuno, Yoshiko; et al.
Abstract: Aims: Cardiovascular disease is the leading cause of death in chronic kidney disease (CKD) patients, although the pathophysiological mechanisms are not fully studied. This study aimed to determine whether CKD could adversely affect subclinical left heart function in a sample of the general population without cardiac disease. Methods and results: We examined 1158 participants who voluntarily underwent extensive cardiovascular examination including laboratory test and two-dimensional speckle-tracking echocardiography to assess left ventricular global longitudinal strain (LVGLS) and left atrial (LA) reservoir, conduit, and pump strain. According to the estimated glomerular filtration rate (eGFR), participants were classified into four groups; Stage 1 ( n = 112; eGFR ≥90 mL/min/1.73 m 2 ), Stage 2 ( n = 818; 60–89 mL/min/1.73 m 2 ), Stage 3a ( n = 191; 45–59 mL/min/1.73 m 2 ), and Stage 3b–5 ( n = 37; eGFR <45 mL/min/1.73 m 2 ). Progressive declines of LVGLS, LA reservoir, and conduit strain were observed according to the severity of CKD ( P < 0.001), while LA pump strain did not differ between the groups. In multivariable analyses, eGFR was associated with LVGLS (standardized β = −0.068, P = 0.019) as well as LA reservoir (standardized β = 0.117, P < 0.001) and conduit strain (standardized β = 0.130, P < 0.001), independent of traditional cardiovascular risk factors, pertinent biomarkers, and LV geometry and diastolic function. The independent association between eGFR and LA strain persisted even after adjustment for LVGLS. Conclusion: Worsening renal function was independently associated with impaired LV/LA strain in an unselected community-based cohort. The assessment of LV and LA strain may allow better risk stratification in CKD patients. Graphical Abstract: